Comparison of One-year Survival Rate of Hip Arthroplasty Performed within and After 72 Hours in Elderly Femoral Neck Fracture - Suttaphakti, Burin; Tananoo, Sirikarn; Thremthakanpon, Witoon; Wanitcharoenporn, Wiboon (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: Hip fracture is a common cause of mortality in the elderly. Our study compared the one-year mortality rate in elderly femoral neck fracture who received hip arthroplasty between an early (<72 hours after admission) and delayed group (≥ 72 hours after admission). Methods: Eighty-one patients were included in the prospective cohort study. The type of operation (total hip arthroplasty or bipolar hemiarthroplasty/cemented or cementless arthroplasty) was chosen as indicated in standard treatment, depending on a patient’s cognitive function, ambulatory status, and comorbidities. Results: The sample was 81 patients (44 in the early and 37 in the delayed groups). The one-year mortality rate was 9.9% (4.5% in the early and 16.7% in the delayed group; P =0.079). The mean survival time was 11.47 months (11.97 months in the early and 10.88 months in the delayed group (P= 0.094, HR = 3.93)). Operations performed within 72 hours decreased the one-year mortality rate. Subgroup analysis showed that the early surgery group had a lower one-year mortality rate than the delayed group without preoperative medical conditions (P = 0.011, HR = 8.08). Conclusions: There was no significant difference in the one-year mortality rate between the early and delayed surgery groups. Early surgery was associated with improved mean survival time and a significant reduction in one-year mortality in elderly patients with femoral neck fractures. Early surgery is recommended for these patients to reduce immobilization time, postoperative complications and improve survival.